Efficient Homodifunctional Bimolecular Ring‐Closure Method for Cyclic Polymers by Combining RAFT and Self‐Accelerating Click Reaction. Issue 15 (31st May 2017) - Qu, Lin; Sun, Peng; Wu, Ying; Zhang, Ke; Liu, Zhengping
Abstract : A metal‐free homodifunctional bimolecular ring‐closure method is developed for preparing cyclic polymers by combining reversible addition–fragmentation chain transfer polymerization and self‐accelerating double strain‐promoted azide–alkyne click (DSPAAC) reaction. The self‐accelerating property of the DSPAAC ring‐closing reaction facilitates this novel method to efficiently produce pure cyclic polymers by virtue of an excess molar amount of smaller linkers to ring‐close the corresponding linear polymer precursors. Abstract : An efficient metal‐free homodifunctional bimolecular ring‐closure method is developed for the formation of cyclic polymers by combining reversible addition‐fragmentation chain transfer (RAFT) polymerization and self‐accelerating click reaction. In this approach, α, ω‐homodifunctional linear polymers with azide terminals are prepared by RAFT polymerization and postmodification of polymer chain end groups. By virtue of sym‐dibenzo‐1, 5‐cyclooctadiene‐3, 7‐diyne (DBA) as small linkers, well‐defined cyclic polymers are then prepared using the self‐accelerating double strain‐promoted azide–alkyne click (DSPAAC) reaction to ring‐close the azide end‐functionalized homodifunctional linear polymer precursors. Due to the self‐accelerating property of DSPAAC ring‐closing reaction, this novel method eliminates the requirement of equimolar amounts of telechelic polymers and small linkers in traditional bimolecular ring‐closure methods. It facilitates this method to efficiently and conveniently produce varied pure cyclic polymers by employing an excess molar amount of DBA small linkers.